Battlefield : social representations of commercial sex work on transvestite and transsexual females in Brazil = Sobre campos de batallas : representaciones sociales del comercio sexual entre mujeres auto-identificadas como transexuales y travestis brasileñas - Caravaca Morera, Jaime Alonso 1986- (2018)
To analyze commercial sex work's social representations among Brazilian women who identify as transvestite or transsexual. Methods: A qualitative study with a descriptive and analytical approach based on the Theoretical Paradigm of Social Representation with a structural approach. The sample group was formed by 100 women who defined themselves as transvestite and transsexual in Santa Catarina, Brazil. The data was gathered from September to December 2016 via a questionnaire using the technique of free association of words, as well as semi-directed interviews. Results: Through both prototypical and content analysis, it was confirmed that the most likely elements that formed the core of the social representation were: violence, drugs, risk, work, sadness, prejudice, and danger. In the objectification/objectivation process of commercial sex work, the image shows a mix between daily activities in the streets - which they consider to be their battlefield - and their own feelings and experiences of vulnerability in other areas of society, starting with families, churches, schools and the like. Conclusions: By experiencing commercial sex work, female transvestite and transsexual individuals reveal how the elements that form the social representation are of paramount importance in the legitimation, legalization, and simplification of their identities.
Analizar las representaciones sociales del comercio sexual entre mujeres auto-identificadas como travestis y transexuales en Brasil. Métodos: Estudio cualitativo de naturaleza descriptivo-analítico que, utilizó el Paradigma Teórico de las Representaciones Sociales con abordaje estructural como Referencial Teórico. La muestra fue constituida por 100 mujeres auto-identificadas como travestis y transexuales en Santa Catarina/Brasil. Los datos fueron recolectados de septiembre a diciembre de 2016, por medio de la utilización de un cuestionario auto-administrado que utilizó la técnica de asociación libre de palabras y, por medio de entrevistas semi-directivas. Resultados: A partir del análisis prototípico y de contenido se verificó que los elementos probables que formaron el núcleo central de la representación social fueron: violencia, drogas, riesgo, trabajo, tristeza, prejuicios y peligro. En el proceso de objetificación/objetivación de la prostitución, la imagen refleja un compaso entre sus itinerarios cotidianos en el campo de batalla y los sentimientos y vivencias de vulnerabilidad en los otros espacios institucionales de la sociedad. Conclusiones: la experiencia del comercio sexual de mujeres travestis y transexuales reveló cómo los elementos formadores de la representación social son cruciales en el proceso de legitimación, normatización y simplificación de sus identidades.
En Revista Actualidades en Psicología, Vol. 32, no. 125 (julio - diciembre 2018)
Descripción basada en el contenido visto el 29 de junio 2023.
Keywords: PROSTITUCION -- ASPECTOS SOCIALES; MUJERES TRANSGENERO; TRANSEXUALIDAD -- ASPECTOS SOCIALES; VULNERABILIDAD SOCIAL; IDENTIDAD SEXUAL -- ASPECTOS SOCIALES